Analisis Desain Permanent Magnet Synchoronous Generator 12 Slot 8 Pole dengan Membandingkan 3 Material Stator dan Rotor Menggunakan Software Magnet Infolytica - Didin; Mustarum Musaruddin; Wa Ode Siti Nur Alam (Jurusan Teknik Elektro Fakultas Teknik Universitas Halu Oleo, 2023)
This study analyses the design of a 12 slot 8 pole permanent magnet synchronous generator by comparing 3 stator and rotor materials. This research uses Finite Element Method (FEM) based software, Magnet Infolytica. FEM is a method used to solve problems about complex electromagnetics, so that it can be solved by analytical models, especially those related to non-linear properties of materials. In this study, 3 types of materials were used, namely Carpenter: silicon steel, Megaperm 40L and Vocaflux 48. The three generators with different stator and rotor materials were simulated using Magnet Infolytica 7.5 software. No-load simulation output results for 3 types of materials namely Carpenter: silicon steel of 279 VDc, Megaperm 40L of 265 VDc and Vocaflux48 of 261 VDc. For load testing, a load variation of 100Ω, 50Ω, and 25Ω is given. The results obtained that the material that produces the best output is Carpenter: silicon steel material which produces output at 100Ω load of 2.94 A, 294.20 VDc, -8.64 Nm and efficiency of 88%. At 50Ω load of 5.28 A, 264.30 VDc, -14.59 Nm, and efficiency of 86%. While at a load of 25Ω, the output is obtained at 8.74 A, 218.60 VDc, -21.16 Nm, and an efficiency of 81%.